Investigating the Correlation Between Vocabulary Mastery and Narrative Reading Comprehension Among EFL University Students - Andi Candra Kurniawan; Eko Suhartoyo; Mochamad Imron Azami (AL-ISHLAH: Jurnal Pendidikan, 2026)
Vocabulary knowledge plays a fundamental role in reading comprehension because it enables learners to recognize lexical meanings and construct textual understanding. Although previous studies have consistently reported a positive relationship between vocabulary knowledge and reading comprehension, limited evidence has specifically examined this relationship among Indonesian EFL university students using semantic aspects of vocabulary mastery. This study investigated the correlation between vocabulary mastery and narrative reading comprehension among fourth-semester students in the English Education Department at Universitas Islam Malang. A quantitative correlational design with an ex post facto approach was employed. Twenty-nine students participated through total sampling. Data were collected using two validated multiple-choice tests measuring vocabulary mastery (synonyms, antonyms, and contextual meanings) and narrative reading comprehension (main ideas, explicit and implicit information, contextual meaning, and text structure). Descriptive statistics and Pearson's Product-Moment Correlation were performed using IBM SPSS after the normality assumption had been satisfied. The findings revealed that the participants achieved a mean score of 68.62 in vocabulary mastery (fair) and 83.10 in reading comprehension (good). Pearson's correlation analysis indicated a statistically significant positive relationship between vocabulary mastery and reading comprehension (r = 0.398, p = 0.032). The coefficient of determination (r² = 0.158) showed that vocabulary mastery explained 15.8% of the variance in reading comprehension. Vocabulary mastery is positively associated with narrative reading comprehension; however, its contribution is modest, indicating that reading comprehension is influenced by additional linguistic and cognitive factors. The findings highlight the importance of integrating explicit vocabulary instruction into university EFL reading courses to support students' academic reading proficiency.